DOP28 Medical and Surgical Outcomes in Isolated Internal Penetrating Crohn's Disease: A Multi-Centre Experience. (27th May 2021) - Sebepos-Rogers, G; Fragkos, K; Shakweh, E; Shah, K; Lake, L; Balarajah, S; Chung, Y; McGuire, J; Al-Shakarchi, N; Khetan, T; Bottle, J; Anandarajah, C; et al.
Abstract: Background: Isolated internal penetrating Crohn's diseases (IIPCD) is the second most common fistulating phenotype yet remains poorly characterised in therapeutic trials. This study assessed long-term outcomes of IIPCD. Methods: We performed a retrospective study on data collected from 6 IBD referral centres, screening imaging reports between January 2016 and April 2019, excluding perianal or enterocutaneous fistulation, resulting in 121 patients with IIPCD. Management was classified as no intervention, medical (new/optimised) or surgical. The primary endpoint was complete resolution (CR) of fistula at next two imaging reassessments, paired with symptom and nutrition status, as previously defined(Samimi et al., 2010). Secondary endpoint was combined CR and partial resolution (PR). Statistics: Fisher's exact, Kaplan-Meier method (SPSS v.27). Results: Of patients at IIPCD diagnosis, 21% had previous IBD-related surgery, 21% were on a current biologic, 41% immunomodulator and 41% no treatment. Fistulae were majority enteroenteric (55%) and enterocolonic (48%), minority genitourinary (7.4%), with median disease duration at IIPCD diagnosis of 64 months. Outcomes of 118 patients with ≥1 interval imaging were analysed. Initial management was: 25.4% ( n =30) no intervention, 49.2% ( n =59) medical, 25.4% ( n =30) surgical. Of fistula characteristics, only abscess predicted surgery over medical management (OR 5.30, 95% CI 1.60–15.48 p =0.0061), Figure 1. At first reassessment, CR and PR for the three management cohorts was 13.3%, 12.1%, 66.7% and 20.0%, 46.6%, 26.7%, respectively. The cumulative probability of CR was significantly greater for surgery compared with no intervention and medical management (log-rank p <0.001), Figure 2, and sustained when excluding pre-existing biologic (log-rank p =0.007), Figure 3, or previous surgery history (log-rank p <0.001). As observed management was then adjusted, cohorts were re-stratified: 13.5% ( n =16) no intervention only, 45.8% ( n =54) any medical but no surgery, 40.7% ( n =48) any surgery. At second reassessment, again surgery significantly predicted CR over other management (log-rank p <0.001), Figure 4, but this was lost using the less strict outcome of combined CR and PR (log-rank p =0.447). No baseline variables were predictive of CR by each management. 27.6% (16/58) and 6.7% (2/30) of initial medical and no intervention cohorts had subsequent surgery (median interval 6.7 and 50.1 months) but there was no significant difference in peri-operative parenteral nutrition or post-operative intra-abdominal septic complication rates between earlier or later surgery. Conclusion: In this cohort, surgery increases the probability of resolution of IIPCD with medical therapy including biologics offering limited temporising effect.